Kerja Sama Indonesia Jepang di Bidang Otomotif : Toyota Kijang sebagai Simbol Inovasi dan Kemitraan Strategis - Jayana, Alexander Rabbani Adhi; Rahman, Muhammad Alif Luthfi; Samosir, Ericsson (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Cooperation between Indonesia and Japan in the automotive industry, particularly through the development of the Toyota Kijang, is an example of strategic collaboration that has successfully supported economic and technological growth. This research aims to analyze the dynamics of this bilateral cooperation, focusing on achievements and challenges in technology transfer, strengthening local industries, and the resulting socio-economic impacts. The research method uses a qualitative literature study that refers to theories of global political economy, mercantilism, international cooperation, and international business. The results show that Toyota Kijang has successfully become a symbol of innovation and economic integration between the two countries. However, dependence on Japanese technology, barriers to technology transfer, and unequal distribution of benefits are the main challenges. To overcome this, it is recommended that technology transfer policies be strengthened, collaboration between the education and industry sectors be made, international cooperation partners be diversified, and investment in green technology research increase. These steps are expected to improve the competitiveness of Indonesia's automotive industry and encourage more sustainable cooperation in the future.